2013
DOI: 10.1002/rsa.20519
|View full text |Cite
|
Sign up to set email alerts
|

Tight Hamilton cycles in random hypergraphs

Abstract: Abstract. We give an algorithmic proof for the existence of tight Hamilton cycles in a random r-uniform hypergraph with edge probability p = n −1+ε for every ε > 0. This partly answers a question of Dudek and Frieze [Random Structures Algorithms], who used a second moment method to show that tight Hamilton cycles exist even for p = ω(n)/n (r ≥ 3) where ω(n) → ∞ arbitrary slowly, and for p = (e + o(1))/n (r ≥ 4).The method we develop for proving our result applies to related problems as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(76 citation statements)
references
References 24 publications
1
75
0
Order By: Relevance
“…We remark that our proof of Theorem 2 also yields a deterministic polynomial time algorithm for finding a copy of the kth power of the Hamilton cycle. The proof technique (see Section 2.2 for an overview) is partly inspired by the methods used in [2] (which have similarities to those of Kühn and Osthus [28]). …”
Section: Our Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We remark that our proof of Theorem 2 also yields a deterministic polynomial time algorithm for finding a copy of the kth power of the Hamilton cycle. The proof technique (see Section 2.2 for an overview) is partly inspired by the methods used in [2] (which have similarities to those of Kühn and Osthus [28]). …”
Section: Our Resultsmentioning
confidence: 99%
“…For the first task, we make use of the reservoir method developed in [2] (see also [28] for a similar method). In essence, the fundamental idea of this method is to ensure that P ′ contains a sufficiently big proportion of vertices which are free to be taken out of P ′ and used otherwise.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…When, later in the proof, we need to use some vertices from the reservoir set, we use the deterministic graph G α to swap out some vertices from the reservoir. Similar kind of reservoir structures were used for embedding bounded degree trees [18] and tight Hamilton cycles in hypergraphs [2], but we use the interplay of the random and deterministic graphs in a new way to create this structure.…”
Section: Preparing the Reservoirmentioning
confidence: 99%
“…Using the second‐moment method, Dudek and Frieze have shown that 1/n is a threshold for the appearance of a tight Hamilton cycle in a random k ‐graph for any k3. An algorithmic proof for pn1+ɛ was given by Allen, Böttcher, Kohayakawa and Person , for any constant ɛ>0. The next theorem, again, lies between these two results: the bound on p is a logarithmic factor away from the optimal one and we obtain a quasi‐polynomial algorithm (instead of a polynomial one which requires p to be a factor of nɛ away from the smallest possible value, as in ).Theorem Let k2 be an integer.…”
Section: Introductionmentioning
confidence: 99%